Brave new words : how AI will revolutionize education (and why that's a good thing) - Khan, Salman, 1976- (Viking, an imprint of Penguin Random House LLC, 2024)
"From the founder of Khan Academy, the first book written for general audiences on the AI revolution in education, its implications for parenting, and how we can best harness its power for good"--